2021
DOI: 10.1097/bsd.0000000000001271
|View full text |Cite
|
Sign up to set email alerts
|

Propensity Scored Analysis of Outpatient Anterior Lumbar Interbody Fusion

Abstract: Objective: The aim were to (1) evaluate differences in postoperative outcomes and cost associated with outpatient anterior lumbar interbody fusion (ALIF) compared with inpatient ALIF, and to (2) identify independent factors contributing to complications after outpatient ALIF.Summary of Background: While lumbar fusion is traditionally performed inpatient, outpatient spinal surgery is becoming more commonplace as surgical techniques improve. Methods:The study population included all patients below 85 years of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Moreover, Parrish et al 22 described a series of outpatient ALIF procedures and found that those patients were less likely to have a diagnosis of herniated nucleus pulposus, less likely to have degenerative disk disease along with foraminal stenosis, less likely to have pathology at L4-5, and less likely to have retrolisthesis or lateral listhesis. Kamalapathy et al 25 reported in ALIF patients, older patients, patients with BMI more than 30, and those with a higher comorbidity burden were more likely to undergo inpatient procedures. Blaginykh et al 19 investigated the NSQIP database and found that outpatient PLF patients were younger and less likely to be receiving steroid therapy, but were more likely to have high BMI and diabetes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Parrish et al 22 described a series of outpatient ALIF procedures and found that those patients were less likely to have a diagnosis of herniated nucleus pulposus, less likely to have degenerative disk disease along with foraminal stenosis, less likely to have pathology at L4-5, and less likely to have retrolisthesis or lateral listhesis. Kamalapathy et al 25 reported in ALIF patients, older patients, patients with BMI more than 30, and those with a higher comorbidity burden were more likely to undergo inpatient procedures. Blaginykh et al 19 investigated the NSQIP database and found that outpatient PLF patients were younger and less likely to be receiving steroid therapy, but were more likely to have high BMI and diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…In most of the studies in which an outpatient or ambulatory cohort was compared to an inpatient cohort, the outpatient/ambulatory arm was found to have either lower or similar odds of a complication 10,12,14,15,18,24,25. Only one paper, Arshi et al ,5 did report statistically significant higher rates of complications for the outpatient group compared to the inpatient group following a PLF procedure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 ALIF has demonstrated safety and efficacy when compared to other approaches, even in the ambulatory setting. 17,19,20 However, there is little-to-no published data regarding the influence of gender on outcomes following ALIF. As Gianakos et al (2020) posited, it is necessary to have a better understanding of the influence gender has on spine surgery to provide equitable healthcare to both female and male patients alike.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies with a total of 70,000 IPS patients and 5043 OPS patients were included for revision surgery. 18,[20][21][22]24,25,27,29,30 The Pooled revision surgery rate was 1.9% (0%-30%) in the OPS cohorts and 3% (0%-24%) in the IPS cohorts. The metaanalysis of 9 studies showed no significant difference in revision surgery rates between inpatient and outpatient fusion [OR = 0.81 (0.57-1.15), P = 0.239, I2 = 65.2%] (Fig.…”
Section: Readmission and Revision Surgerymentioning
confidence: 96%